Dynamics and density distribution of laser-produced Al plasmas using optical interferometry and optical emission spectroscopy. (March 2019) - Cao, Shiquan; Su, Maogen; Min, Qi; Sun, Duixiong; Ma, Pengpeng; Wang, Kaiping; Jiao, Zhihong; Dong, Chenzhong
Highlights: Two different diagnostic methods, optical interferometry and OES were used to investigate laser-produced Al plasmas in air at atmospheric pressure. Three-dimensional spatial expansion profiles of the plasma plume and shock wave of laser-produced Al plasmas in air at atmospheric pressure were presented. 2D electron density distributions of Al plasmas were obtained from the spatial dependence of the refractive index of plasma. Consistency of the results of optical interferometry and OES was verified and the advantages and disadvantages of the two diagnostic methods were discussed. Abstract: The dynamic evolution and density distribution of laser-produced plasmas (LPP) of Al in air at atmospheric pressure were investigated using optical interferometry and optical emission spectroscopy, respectively. Interferograms were obtained in Mach–Zehnder interferometry with a laser pulse energy of 35 mJ and delay times from 200 ns to 6.9 µs. From the shift in interference fringes within this time interval and Taylor–Sedow theory, the expansion profiles of the shock wave were found to be hemispherical and approached planar propagation. The expansion and evolution of the plasma plume were also studied by exploiting the phase shift and refractive index obtained from the interferograms using the fast Fourier transformation and Abel transformation. Three-dimensional spatial expansion profiles of the plasma plume and shock wave were presented. In addition, two-dimensional electron density distributions of the Al plasmas were obtained from the spatial dependence of the refractive index of plasma, and compared with the results of optical emission spectroscopy. The results from the two diagnostic methods and their advantages and disadvantages are discussed. This work exploits two diagnostic methods to study the dynamic evolution and the density distribution of the LPP in air at atmospheric pressure and provides an important base reference for developing LPP applications in many fields.